Growth Dynamic of Allogeneic and Autogenous Bone Grafts in a Vertical Model - Lima,Julio Leonardo de Oliveira (2018)
Abstract Several techniques have been proposed for vertical bone regeneration, and many of them use bone autogenous and allogeneic grafts. The purpose of this study was to compare demineralised freeze-dried bone allografts (DFDBA), fresh-frozen (FF) allografts, autogenous bone grafts to find differences between volumetric and histological quantity of bone formation and vertical bone growth dynamic. A vertical tissue regeneration bone model was performed in rabbit calvarias under general anaesthesia. Four hollow cylinders of pure titanium were screwed onto external cortical bone calvarias in eight rabbits. Each one of the cylinders was randomly filled with one intervention: DFDBA, FF, autogenous bone, or left to be filled with blood clot (BC) as control. Allogeneic grafts were obtained from a ninth animal following international standardised protocols for the harvesting, processing, and cryopreservation of allografts. Autogenous graft was obtained from the host femur scraping before adapting hollow cylinders. Animals were euthanized at 13 weeks. Vertical volume was calculated after probe device measurements of the new formed tissue inside the cylinders and after titanium cylinders were removed. Histomorphometry and fluorochrome staining were used to analyse quantity and dynamic of bone formation, respectively. Results showed that DFDBA and fresh-frozen bone improved the velocity and the quantity of bone deposition in distant portions of the basal plane of grafting. Remaining material in allograft groups was more intense than in autogenous group. Both allografts can be indicated as reliable alternatives for volume gain and vertical bone augmentation.